An Analysis of Activity Based Costing Practices in Selected Manufacturing Units in India - Arora, Amit Kumar; Raju, M. S. S. (Indian Journal of Finance, 2018)
This study was an attempt to analyze the motives for implementation and causes for non implementation of activity based costing (ABC) system and to establish the relationship between the company characteristics and use of the ABC system in selected manufacturing units in India. The study targeted medium and large scale companies having at least 100 employees and a minimum investment of Rs. 5 crores in plant and machinery. Logistic regression and descriptive statistics were performed to analyze the data through SPSS. The study found a number of employees and the percentage of overheads as significant company characteristic factors for the implementation of the ABC system. More adequate pricing decisions, better overhead cost allocation, and more accurate product cost were found as the motives for the implementation of the ABC system. The major challenges faced during the adoption process of the ABC system are selecting cost drivers, high cost of ABC, data collection difficulties, and uncertainty of ABC benefits. Costly to switch to ABC, easy to track cost, satisfied with current system, and uncertainty of ABC benefits were found as the main causes for non adoption of ABC. The study recommended the implementation of the ABC system to get the various benefits associated with it.